1807. The Impact of Rapid Diagnostic Testing and Antimicrobial Stewardship on the Time to Escalation/De-escalation of Antimicrobial Regimens for Gram-Negative Bloodstream Infections at a Large Community Hospital. (26th November 2018) - Gawrys, Gerard W; Lee, Grace C; Tun, Khine; Meckel, Jordan; Zheng, Connor
Abstract: Background: Prompt identification of an etiologic pathogen is vital for the optimal management of bloodstream infections (BSIs). Rapid diagnostic testing (RDT) has implications for the treatment of BSIs, particularly for cases with resistant Gram-negative (GN) organisms. The purpose of this study was to assess the impact of Verigene's Gram-negative blood culture nucleic acid test (BC-GN), in conjunction with a pharmacy-driven antimicrobial stewardship team (AST), on time to antimicrobial optimization in GN BSIs. Methods: This was a retrospective pre- and post-intervention study at a 950-bed community hospital in South Texas. Clinical isolates from adult patients with GN BSIs were included across two study periods: from July 1, 2012 to July 31, 2014 in the pre-intervention group (prior to BC-GN with AST) and from July 1, 2015 to July 31, 2017 in the post-intervention group (after BC-GN with AST). RDT results were transmitted to pharmacy-managed surveillance software for AST review and intervention. The primary outcome was time to optimal therapy (TOT) from initial culture positivity. Secondary outcomes included TOT based on organism and clinical pharmacy staffing hours, hospital length of stay, and all-cause mortality. Results: Among 324 patients screened with a first episode of GN BSI, 121 and 119 patients were included in the pre- and post-intervention groups, respectively. Apart from intensive care unit admission at the time of culture collection, there were no significant differences in baseline characteristics between the two groups. The post-intervention group had a significantly shorter TOT (60.2 ± 36.0 hours vs. 29.0 ± 24.0 hours, P < 0.001). Notably, time to escalation for patients with third-generation cephalosporin-resistant isolates was significantly shorter in the post-intervention group (48 ± 36.0 hours vs. 19.2 ± 16.8 hours, P < 0.01). In the post-intervention group, TOT was significantly shorter during fully staffed clinical pharmacy hours vs. reduced clinical pharmacy staff hours (18.48 ± 31.2 hours vs. 31.44 ± 38.4 hours, P = 0.014). No differences were seen in length of stay or all-cause mortality. Conclusion: The implementation of RDT with a pharmacy-driven AST substantially decreased TOT for GN BSIs. This study also highlights the positive impact of clinical pharmacy staff on shorter TOTs. Disclosures: All authors: No reported disclosures.